Distribution, Sedimentology and Origin of Mineralogical Assemblages from a Continental Na-bentonite Deposit in the Cretaceous Neuquén Basin (Argentina) - Musso, Telma Belén (2022)
Collected samples of bentonite and associated facies from the Justina deposit of Cretaceous age (Anacleto Formation) have been studied. Facies analysis, mineralogical, and geochemical studies have been carried out using several techniques, including: XRD, FTIR, DTA-TGA, microscopy (OM, SEM-EDX), and chemical analysis. The deposit occurs in a shallow, saline lacustrine environment developed over a fluvial floodplain, with a thickness between 0.21 and 0.8 m intercalated between fine-grained siliciclastic facies. Three mineral assemblages were found. In assemblage 1, the bentonite has low content of detrital minerals and the smectite is sodic. In assemblage 2, the bentonite shows the occurrence of minor analcime and mica, slightly higher detrital mineral content and the smectite is sodic to sodic-calcic. The associated detrital facies (assemblage 3) is dominated by illite and a mixed layer of illite and calcic smectite (R0), subordinately kaolinite + chlorite, and locally low-ordered smectite. As inherited minerals are found: quartz, potassium feldspar, plagioclase, illite-mica, heavy minerals (monazite, zircon, apatite, titanomagnetite) and volcanic rock fragments (andesite, glass). Authigenic minerals are: sodium smectite, analcime, barite, celestine, gypsum, and hematite. A model for the formation of authigenic minerals is proposed, highlighting the formation of sodic smectite from the alteration of volcanic glass of trachyandesitic composition.